ANALISIS PENYERAPAN TENAGA KERJA PADA USAHA PERCETAKAN FOTO COPY DI KOTA KENDARI - Takyuddin, Muh. (JURNAL EKONOMI UHO, 2016)
This study aims to determine workers absorbed on printing business in Kendari. The study used primary data with 10 sample of printing business. This study used descriptive analysis. Based on the results and discussion show that workers absorbed on 10 business printing is 70 workers. The wages offered by a photo copy printing business in Kendari is lower than the regional minimum wages. The lower wage does not affect on worker behaviour to labor supply